Post-Thyroid Surgery Complications in Patients with Palpable Thyroid Gland - Muhammad Imran Bhatti, Saad Abdur Rehman Afaque, Zubair Anwar, Muhammad Razzaq Dogar, Abdul Waheed, Tatheer Syed, Adnan Anwar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the rate of post-thyroid surgery complications in patients with a palpable thyroid gland. Study design and setting: Cross sectional observational, Department of ENT, Jinnah Postgraduate Medical Center, Karachi. Methodology:Patients were enrolled from OPD and wards. Patients with palpable thyroid gland with plan for thyroid surgery were included. Thyroid surgery was performed by a surgeon having >5 years of experience. Patients were discharged by 48–72 hours postoperatively. All patients had their vocal cords checked at the time of extubation. On the follow-up visit at day 5, final diagnosis of complications was assessed. For data analysis, SPSS v23.0 was used. Cross tabulation was done with type of surgery (lobectomy, isthmusectomy, subtotal thyroidectomy, near total thyroidectomy and total thyroidectomy) to see effect of these on outcome variables by applying chi square test. A p-value ≤0.05 was taken as significant. Results:Total 157 patients with palpable thyroid gland were selected for this study. Mean age of the patients was 39.8±12.2 years. Total 112(71.3%) were males and 45(28.7%) were females. Out of 157 patients, 14(8.9%) had hypoparathyroidism, while, 72(45.9%), 40(25.5%), 16(10.2%) and 15(9.6%) had hypothyroidism, hyperthyroidism, RLN paralysis and airway obstruction respectively. Conclusion:More extensive procedures are associated with greater number of complications in thyroid surgery. Complications of thyroid surgery can be minimized by sound knowledge of normal and pathologic anatomy and an unhurried, gentle operation technique. Keywords: Thyroidectomy, Post-thyroid Surgery Complications, Lobectomy, Isthmusectomy, Subtotal Thyroidectomy